2019
DOI: 10.1101/589713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood socio-economic disadvantage predicts reduced myelin growth across adolescence and young adulthood

Abstract: 37Socio-economic disadvantage (SED) increases exposure to life stressors. Animal research suggests 38 early life stressors affect later neurodevelopment, including myelin developmental growth. To 39 determine whether human childhood SED affects myelination in adolescence and early adulthood we 40 measured the developmental increase of a sensitive myelin marker, magnetization transfer (MT), in a 41 longitudinal study. Childhood SED was associated with globally reduced MT, as well as slower intra-42 cortical MT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To investigate the maturational trajectory of model-based control, we used these estimates of model-based control, computed separately at each assessment, as dependent variables in a linear mixed-effects (LME) model. This model was informed by analysis recommendations ( 36 ) successfully adopted in recent studies ( 37 , 38 ) ( Materials and Methods and SI Appendix ). This tested jointly how model-based control varies with mean age of subjects (i.e., age mean, between-subject effect of age) and how it changes over time (i.e., visits/time, within-subject effect of age), as well as their interaction ( Materials and Methods and SI Appendix , Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the maturational trajectory of model-based control, we used these estimates of model-based control, computed separately at each assessment, as dependent variables in a linear mixed-effects (LME) model. This model was informed by analysis recommendations ( 36 ) successfully adopted in recent studies ( 37 , 38 ) ( Materials and Methods and SI Appendix ). This tested jointly how model-based control varies with mean age of subjects (i.e., age mean, between-subject effect of age) and how it changes over time (i.e., visits/time, within-subject effect of age), as well as their interaction ( Materials and Methods and SI Appendix , Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate developmental changes of model-based control, we used the estimated coefficients of the reward by transition interaction at each time point in the context of LME modeling. We followed analysis recommendations ( 36 ) successfully adopted in recent studies from this sample ( 37 , 38 ) (see also SI Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Such anticipation is closely guided by the engrams of powerful experiences 4 . Harmful engrams are inscribed by "toxic" environments -be it family, educational setting, work, a virtual community on social media or general societal factors like gender or race (Zadow et al, 2021;Ziegler et al, 2020). What is also true is that the brain can adjust to an improved, safer, caring environment whether it is due to lower levels of stress or through learning and enhanced problem solving skills, through a different selfrepresentation etc.…”
Section: Psychopathology Versus Neurodiversitymentioning
confidence: 99%
“…Another important, recent development is the introduction of neuroimaging sensitive to molecular processes, rather than just macroscopic anatomy. One study showed that growing up in a deprived neighbourhood before the age of 12 was associated with slower growth of a myelin-sensitive marker in adolescence (Ziegler et al, 2020); that this was independent of a number of covariates such as IQ, parental occupation and positivity of parenting; but that it was partly mediated by parental education (see Figure 1). The sample in this study was screened for absence of psychiatric and neurological disorder, and no participants fulfilled the World Bank definition of poverty (not having enough to fulfil basic needs).…”
Section: Harm To Brainmentioning
confidence: 99%
“…Yes, because new experimental work will allow to systematically probe different systems and thus empower us to more decisively draw conclusion in terms of symptom relationships. Taken together, both lines of investigations can allow us to test whether the contributions of multiple systems differ in impulsive and compulsive disorders and whether those differences are reflected in separate neural systems associated with compulsivity and impulsivity (14,15). In the long run, a multi-facetted differentiation of patients may be of clinical importance to design treatments, e.g.…”
mentioning
confidence: 99%